Peningkatan Kadar Protein Terlarut pada Larutan Tepung Jagung Menggunakan Saccharomyces cerevisiae - Siska Tridesianti (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic))
Poultry livestock are generally given feed in the form of corn kernels where the corn kernels contain high carbohydrates but have deficiencies of several amino acids. Amino acid deficiency can be overcome by increasing the protein content in the corn kernels. One way to increase the protein content in corn kernels is to carry out a fermentation process in corn flour solution. Therefore, this study aims to determine the effect of corn starch solution to increase dissolved protein levels in Saccharomyces cerevisiae biomass through a fermentation process. This study used a completely randomized design consisting of 8 treatments and 3 replications. The treatment volumes of corn flour solution were 0 mL, 5 mL, 10 mL, 15 mL, 20 mL, 25 mL, 30 mL and 35 mL. Data analysis used the calculation of variance and the BJND test. The results showed that the highest average dissolved protein content and total cell biomass of S. cerevisiae in the 15 ml treatment were 13.52%/g and 15.63 x 107 CFU/mL, the lowest average was in the 35 ml corn flour solution treatment, namely 0. 90%/gr and 3.01 x 107 CFU/mL. Based on the research, it can be concluded that corn flour solution can increase the dissolved protein content in S. cerevisiae biomass up to volume 15 mL/2 mL fermenter through the fermentation process. Based on the results of this study, it can be used as a basis for considering the use of S. cerevisiae fermenters to increase the nutritional value of corn seed-based animal feed.